THE INFLUENCE OF TAX KNOWLEDGE, TAXPAYER AWARENESS, TAX AVOIDANCE AND TAX SANCTIONS ON COMPLIANCE WITH PAYING MOTOR VEHICLE TAXES IN SUBANG CITY - Yuli Maelani (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2023)
The purpose of this study was to determine the effect of tax knowledge, taxpayer awareness, tax avoidance, tax sanctions on compliance with paying motor vehicle taxes. The model used is a Quantitative approach. The sample used was taxpayers in the city of Subang as many as 100 respondents. data collection instruments using primary data. Primary data is obtained using a questionnaire or questionnaire. The analysis method used is validity test and reliability test. Normality test, Multicolonierity Test, and Heteroscedasticity Test. The data analysis technique used in this research is Multiple Linear Regression Analysis, T test, F test and coefficient of determination. The results of partial hypothesis testing show that the variables of tax knowledge, taxpayer awareness, tax sanctions have an effect on motor vehicle taxpayer compliance, while tax avoidance has no effect on motor vehicle taxpayer compliance. And simultaneously the influence of tax knowledge, taxpayer awareness, tax avoidance, tax sanctions has a positive effect on awareness of paying motor vehicle taxes.